Motivação, coping académico e integração social em estudantes atletas - Ricardo Filipe Macedo Silva (2021)
In recent years, in Portugal, the importance that has been given to the school performance of young people has been notorious, as well as to understanding the factors that can create obstacles and/or difficulties in their development and school career. Therefore, it is important to understand which factors most affect students' academic ability. It is clear that stress and the different challenging situations that enhance it will influence their school performance. The way students deal with these stressful school situations is called "academic coping". It is with the support of the Motivational Model of Academic Coping by Skinner et al. that this empirical study emerges, which aims to contribute to a better understanding of coping strategies in the management of everyday academic stressors, as well as its relationship with student's social integration, self-efficacy, and academic engagement and performance. This study also investigated how the practice of a sport can facilitate or hinder the academic coping of students, by comparing the coping strategies of student-athletes with non-athlete students. A total of 164 students from the 8th and 9th grades participated, who were assessed for academic coping (using the Multidimensional Coping Measure), social integration (through the Sociometric Test), school engagement (using the Engagement Scale), self-efficacy (using the MSLQ Self-Efficacy Scale), and academic performance (assessed by averaging their grades in Portuguese and Mathematics). The results showed the expected associations between coping strategies and all the other variables: social integration, self-efficacy, school engagement and performance, and social integration, providing empirical support to E. Skinner's motivational model of academic coping. Results also showed differences between student-athletes and non-athletes in academic coping strategies and social integration. In general, student-athletes tended to use more adaptive coping strategies and their classmates prefer to spend more free time with them than with non-athlete students. This study highlights the relevance that sports practice can have in the way student-athletes manage stressful and challenging situations in the school context and in their social integration.